Epigallocatechin 3-gallate ameliorates bile duct ligation induced liver injury in mice by modulation of mitochondrial oxidative stress and inflammation. - Kezhen Shen; Xiaowen Feng; Rong Su; Haiyang Xie; Lin Zhou; Shusen Zheng (PLoS ONE, 2015)
Cholestatic liver fibrosis was achieved by bile duct ligation (BDL) in mice. Liver injury associated with BDL for 15 days included significant reactive oxygen/nitrogen species generation, liver inflammation, cell death and fibrosis. Administration of Epigallocatechin 3-Gallate (EGCG) in animals reduced liver fibrosis involving parenchymal cells in BDL model. EGCG attenuated BDL-induced gene expression of pro-fibrotic markers (Collagen, Fibronectin, alpha 2 smooth muscle actin or SMA and connective tissue growth factor or CTGF), mitochondrial oxidative stress, cell death marker (DNA fragmentation and PARP activity), NFκB activity and pro-inflammatory cytokines (TNFα, MIP1α, IL1β, and MIP2). EGCG also improved BDL induced damages of mitochondrial electron transport chain complexes and antioxidant defense enzymes such as glutathione peroxidase and manganese superoxide dismutase. EGCG also attenuated hydrogen peroxide induced cell death in hepatocytes in vitro and alleviate stellate cells mediated fibrosis through TIMP1, SMA, Collagen 1 and Fibronectin in vitro. In conclusion, the reactive oxygen/nitrogen species generated from mitochondria plays critical pathogenetic role in the progression of liver inflammation and fibrosis and this study indicate that EGCG might be beneficial for reducing liver inflammation and fibrosis.